SOCIAL NETWORK ANALYSIS OF FAMILY DYNAMICS IN INSTAGRAM REELS COMMENTS ON 'HOME SWEET LOAN' - Moch Yunus Kholis; Catur Nugroho (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explores the dynamics of interaction and information distribution regarding public responses to the Moodkative Instagram Reels video discussing the film 'Home Sweet Loan' through social media network analysis in the video's comment column. The background of this study is based on the increasing discussion about the representation of family dynamics and birth order on social media, which indicates the important role of Instagram as a virtual public space for sharing views and experiences. The purpose of this study is to identify key actors, interaction patterns, and how information about family dynamics and birth order flows among Instagram users. The research method uses Social Media Network Analysis (SMNA) with a population of comments on the Instagram Reels video "Home Sweet Loan". Data collection was carried out by crawling data on comments using the Chrome extension "IG Comment Exporter," followed by analysis using Gephi 0.10.1 software. The results of the study show a communication network consisting of 987 nodes and 209 edges with a diameter value of 3, density 0, reciprocity 0, and centralization 0.00001, describing a decentralized network with minimal and one-way interactions. Key actors such as @septarina.gt, @nina_bollo, and @similarity_28 have significant influence in this network, with interaction patterns dominated by responses to their comments. These findings underscore the important role of social media in disseminating information and shaping public opinion on complex social issues such as family dynamics and birth order.